Entrepreneurship and informal work of venezuelan immigrants, Barranquilla case 2015-2018 - Salas - Hernandez, Isaurys Zareth; Sagbini - Henriquez, Hayleem Sain; Salazar - Araujo, Eduardo José (Universidad Francisco de Paula Santander, 2019)
The present descriptive study, carried out through the analysis of data from secondary sources and a bibliographic review, aims to characterize the entrepreneurial ecosystem of Venezuelan migrants residing in the city of Barranquilla, Colombia, considering variables such as, entrepreneurial ecosystem , informal employment and migration, taking into account the value that the entrepreneurial migrant has, especially in his condition of vulnerability generated by his status as a migrant, being recognized as central actresses for the fulfillment of the Sustainable Development Goals, as they are, end of the poverty, gender equality, decent work and reduction of inequalities, considering that the strengthening of their economic activity is a fundamental pillar for economic growth.